Novel Intraoperative Near-Infrared Fluorescence Camera System for Optical Image-Guided Cancer Surgery - J. Sven D. Mieog; Alexander L. Vahrmeijer; Merlijn Hutteman; Joost R. van der Vorst; Maurits Drijfhout van Hooff; Jouke Dijkstra; Peter J.K. Kuppen; Rob Keijzer; Eric L. Kaijzel; Ivo Que; Cornelis J.H. van de Velde; Clemens W.G.M. Löwik (Molecular Imaging)
Current methods of intraoperative tumor margin detection using palpation and visual inspection frequently result in incomplete resections, which is an important problem in surgical oncology. Therefore, real-time visualization of cancer cells is needed to increase the number of patients with a complete tumor resection. For this purpose, near-infrared fluorescence (NIRF) imaging is a promising technique. Here we describe a novel, handheld, intraoperative NIRF camera system equipped with a 690 nm laser; we validated its utility in detecting and guiding resection of cancer tissues in two syngeneic rat models. The camera system was calibrated using an activated cathepsin-sensing probe (ProSense, VisEn Medical, Woburn, MA). Fluorescence intensity was strongly correlated with increased activated-probe concentration ( R 2 = .997). During the intraoperative experiments, a camera exposure time of 10 ms was used, which provided the optimal tumor to background ratio. Primary mammary tumors ( n = 20 tumors) were successfully resected under direct fluorescence guidance. The tumor to background ratio was 2.34 using ProSense680 at 10 ms camera exposure time. The background fluorescence of abdominal organs, in particular liver and kidney, was high, thereby limiting the ability to detect peritoneal metastases with cathepsin-sensing probes in these regions. In conclusion, we demonstrated the technical performance of this new camera system and its intraoperative utility in guiding resection of tumors.